Pengaruh Pendapatan Domestik Regional Bruto, Indeks Pembangunan Manusia, dan Tingkat Pengangguran Terhadap Kemiskinan di Provinsi Bali - Sukraeni, Ni Putu Enik; Astawa, I Nyoman Widhya; Murthi, Ngurah Wisnu; Marta, I Nyoman Gede (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The issue of poverty requires a precise and sustainable approach as it has become a complex and ongoing problem at both the national and regional levels. So far, development programs have prioritized poverty alleviation. Nevertheless, poverty remains a persistent demographic issue, and addressing it requires appropriate and sustainable strategies. Up until now, development programs have focused on poverty alleviation. However, poverty remains a demographic issue to this day. The data used is secondary time series data from the year 2012 to 2021. The data analysis technique used is multiple linear regression analysis. The research results indicate that: (a) Gross Regional Domestic Product has a partial negative and insignificant effect on poverty in Bali Province. (b) The Human Development Index (HDI) has a partial negative and significant effect on poverty in Bali Province. (c) The unemployment rate has a partial positive and significant effect on poverty in Bali Province. (d) Gross regional domestic product, the human development index, and the unemployment rate simultaneously have a significant effect on poverty in Bali Province.